Programa Bolsa Família: efeitos no desempenho escolar e na superação da vulnerabilidade social de beneficiários em Feira de Santana-BA (2006 - 2012) - Oliveira, Luis Carlos Santos (2014)
This research problematized the relationship between the Bolsa Familia Program - PBF - and education in order to understand whether it has effects in the school life of its beneficiaries as well as their possible effects in overcoming the social vulnerability of beneficiary families. The study was guided by the following question: what are the guidelines of GMP for education and to what extent they become effective and operative mechanisms in the school performance of the beneficiaries and the promotion of overcoming social vulnerability? In the face of this question, the research aimed to examine whether and how the Bolsa Família Program generates effects on school performance and overcoming the social vulnerability of the beneficiary families. With the methodological approach of qualitative research and by means of content analysis, the research used as instruments for data collection documentary sources as minutes of final results of students between 2006 and 2012 lists of beneficiaries students at schools between 2006 and 2012, legislation related to GMP and evaluations conducted by the Ministry of Social Development. Apart from documentary sources semistructured interviews were conducted with five mothers of beneficiary students, selected among those having more time in the program, as well as a questionnaire to school officials. Field data collection occurred at schools whose cognomen was adopted for the research Way of Letters, in the city of Feira de Santana, Bahia. Some categories were important in understanding the movement of the object of research, they being the conception of poverty and social vulnerability. From a critical perspective of the analysis of our social policies, especially targeted policies, among which enters the PBF, to explore the contradictions inherent in the same, the theoretical framework associated to source data allow us to infer that the opposite of guarantees social announced by the Constitution of 1988, linking education as conditionality of Bolsa Família, is within the context of neoliberal policies gain traction in our country in the 90s of last century, with the notable influences in education linking the education as preparation for work and qualification of manpower as a means of activation for the labor market. The survey results showed that the dropout rates of students beneficiaries showed decline in the investigated period. Establishing a comparison between beneficiaries and non students at schools, it was also found between high student beneficiaries failure rates beyond dropout rates higher than those of students beneficiaries in all years analyzed. Specifically following the performance of the five children interviewed mothers was found between the same recurrence and high dropout rate of school failure.